Dental caries management by risk assessment among children - Damyanova, Dobrinka Mitkova; Atanasova, Siyana (International Journal of Public Health Science (IJPHS), 2024)
Dental caries is the highest-frequency oral disease. The purpose of this study is to assess the risk of developing dental caries for groups of children aged three to six in the city of Varna, Bulgaria, taking into account clinical risk factors. The population of this study included 300 children aged 3 to 6 years. Hence, as many 30 children for the experimental and 30 children for the control groups were included in the study with saliva tests. After that, standardized means of decayed, filled surfaces (DFS) index was estimated. The teeth of the children in the experimental group were covered for three months with Clinpro™ White Varnish. The Research Ethics Committee at the MU-Varna University approved the study. We applied the Greene and Vermillion oral hygiene index. Biostatistics was conducted with a specialized package for statistical analyzes was used StatSoft, STATISTICA manual (Software system for data analysis STATISTICA 10.0, 2010. The results in our study show the strong influence of carbohydrate nutrition and poor oral hygiene on the development and progression of the caries process. The results of the study of the frequency of caries lesions on surfaces show a value of 6.35±0.65. Caries lesions on 1 and 2 surfaces predominate (23.75%). Almost 100% of the children in the control group had Streptococcus mutans and a high risk of caries. From the risk assessment results obtained for each child patient, individual prevention programs are prepared for children.